Concrete lintels reinforced with steel fibres oriented by a magnetic field - Carrera, Kristýna; Künzel, Karel; Konrád, Petr; Sovják, Radoslav; Papež, Václav; Mára, Michal; Fornůsek, Jindřich; Kheml, Přemysl (Acta Polytechnica, 2022)
This paper explores the possibility of applying the technique of magnetic orientation of steel fibres for manufacturing a concrete structural element of realistic dimensions, compared to small laboratory specimens. This technique could be a part of an answer to the current need for faster and automated production in the prefabrication industry. The examined specimens have dimensions of commonly used lintels in construction, 80 mm × 100 mm × 980 mm. The properties of specimens with magnetically oriented fibres are compared with same size specimens prefabricated conventionally. The orientation of fibres has been confirmed by Q-factor non-destructive testing method using a measuring coil. All specimens were tested with a four-point bending test. The specimens with oriented fibres show a significantly higher flexural strength, by 150 %, than specimens produced conventionally with the same volume of fibres.